Cezar's Car Wash detailed business plan - Lulkowski Cezary (My University, 2006)
The purpose of the thesis is a presentation of a business plan for Cezar’s Car Wash. The thesis provides market analysis, company description, marketing and sales activities. It describes the products and services as well as management and ownership. The funds and their uses as well as financial data are also provided.
Keywords: business plan; car wash; market analysis; management; marketing and sales activities